Comparison of the clinical effectiveness of zanamivir and laninamivir octanoate for children with influenza A(H3N2) and B in the 2011–2012 season. Issue 2 (19th August 2013) - Koseki, Naoko; Kaiho, Miki; Kikuta, Hideaki; Oba, Koji; Togashi, Takehiro; Ariga, Tadashi; Ishiguro, Nobuhisa
<x xml:space="preserve">Abstract</x> Objectives To evaluate the clinical effectiveness of the two inhaled neuraminidase inhibitors (NAIs), zanamivir (ZN) and laninamivir octate (LO), for influenza A(H3N2) and B virus infections. Design A prospective, multicenter observational study was conducted from January to April in 2012. Setting Outpatients aged 5–18 years who had a temperature of 37.5°C or higher and were diagnosed as having influenza based on an immunochromatographic assay were enrolled. Sample A total of 338 patients treated with ZN and 314 patients treated with LO were compared. Main outcome measures The duration of fever after administration of the first dose of each NAI was evaluated as a primary endpoint. The secondary endpoint was episodes of biphasic fever. Results No statistically significant difference in the duration of fever was found between the ZN and LO groups (log‐rank test, P = 0.117). A logistic regression model showed that episodes of biphasic fever increased by 1.19 times for every decrease of 1 year of age (P = 0.016) and that the number of biphasic fever episodes in patients treated with LO was 5.80‐times greater than that in patients treated with ZN (P < 0.001). Conclusions Although the duration of fever in the LO group was comparable to that in the ZN group, episodes of biphasic fever were more frequent in younger children and in the LO group than in the ZN group.